Membrane Insertion of MoS2 Nanosheets: Fresh vs. Aged - Ye, Rui; Song, Wei; Ou, Xinwen; Gu, Zonglin; Zhang, Dong (Frontiers in Chemistry, 2021)
Fresh two-dimensional molybdenum disulfide (MoS2) can absorb the hydrocarbon contaminations from the ambient air and cause surface aging. Understanding how the aging of surface affects the interaction of MoS2 with biomolecules is crucial for its applications in the biomedical field. Here, employing all-atom molecular dynamics simulations, we investigated the interactions of the fresh and aged MoS2 nanosheets with lipid membranes of different components. Our results show that though both the fresh and aged MoS2 nanosheets can spontaneously insert into the bilayer membrane, the fresh MoS2 nanosheet displays significantly more robust interaction and then has a larger penetration depth than the aged counterpart, regardless of the lipid components. The calculations of potential mean forces through the umbrella sampling further confirm that the insertion of fresh MoS2 nanosheet into the lipid membranes is more energetically favorable. Moreover, we found that the fresh MoS2 nanosheets can cause a larger damage to the integrity of lipid membranes than the aged one. This work provides insightful understandings of the surface-aging-dependent interactions of MoS2 nanosheets with biomembranes , which could facilitate the design of novel MoS2-based nanodevices with advanced surface properties.